Multispecies sensory networks and social foraging strategies: Implications for population decline in procellariiform seabirds - Jesse Granger; Gabrielle Nevitt; Sönke Johnsen (Proceedings of the National Academy of Sciences, 2025)
Multispecies sensory networks, where different species prioritize different sensory modalities and then use heterospecific information in a likely noncooperative fashion, may allow animals to improve foraging over large areas for cryptic prey. We test this hypothesis in procellariiform seabirds that forage in mixed flocks, where both prey odors and visual cues provided by other foraging hetero- and conspecifics might improve success rates. Using agent-based models, we explored the impact of social strategies on olfactory foraging for Antarctic krill ( Euphausia superba ). Our results suggest that social foraging enables species with different sensory adaptations to achieve similar success rates. Additionally, our results indicate that foraging is more successful in mixed-species rather than single-species flocks, where individuals can monitor the activity of other birds that are using different sensory foraging strategies than themselves to find prey. These results suggest that sensory-based foraging networks may be more critical to their survival than previously assumed. Finally, we show that success rates decrease at low population densities. As seabird populations continue to decline, understanding and preserving these social foraging networks may be essential for their conservation and ecological success. Overall, our study provides insights into the critical role of multispecies sensory networks to foraging success, wherein different species have different sensory adaptations for locating prey. While we used empirical anatomical and behavioral data specific to procellariiforms to inform our models, our approach and results may have broader implications for other species as well.